Effect of aeration rate and light cycle on the growth characteristics of Chlorella sorokiniana in a photobioreactor - Magdaong, J. B. (Animo Repository, 2019)
Microalgae is considered to be an important resource to address the global demand for sustainable energy and green technologies. Numerous applications of microalgae have already been identified in the past. They can be cultivated to produce food, animal feeds, nutraceuticals, and even biofuels. They can also be used for environmental applications such as carbon capture and storage, and wastewater treatment. There are different environmental factors that can affect the growth of microalgae such as light, nutrients, temperature, and aeration. Among different microalgae strains, Chlorella sorokiniana had been identified to be one of the most effective and commonly used strains across these different applications. In this study, the effect of aeration rate and light cycle on the growth characteristics of C. sorokiniana in a photobioreactor was investigated. Cultivation experiments were carried out at room temperature (24 - 26 °C) under phototrophic conditions in which the light intensity was set to 150 μmol/m2-s and the carbon source used was air enriched with carbon dioxide at 2.5% concentration. The aeration rates evaluated were 0.0125, 0.0250, 0.0500, 0.1000, and 0.2000 vvm while the light cycles evaluated were 24:0 (continuous illumination), and 12:12 (diurnal illumination). The results showed that in the 24:0 light cycle, increasing the aeration rate up to 0.1000 vvm led to an increase in the cumulative biomass production, specific growth rate, overall biomass productivity, and nitrate consumption of C. sorokiniana cultures. At 0.2000 vvm, no increase in any of these parameters were observed. Meanwhile, the aeration rate did not have any effect on the carbohydrate content of C. sorokiniana. On the other hand, cultivation under a 12:12 cycle resulted in a decrease in all of the parameters across all aeration rates evaluated. However, no significant interaction between the light cycle and the aeration rate was found in this study. Finally, among the conditions evaluated, the 24:0 light cycle and 0.1000 vvm aeration rate led to the best growth characteristics of C. sorokiniana. The results from this study indicate that aeration rate and light cycle have significant effects on cultivating microalgae such as C. sorokiniana. The results also showed that appropriate levels of these factors should be considered depending on the application of the microalgae cultivation. For future work, the growth of C. sorokiniana can be modeled to dynamically optimize these factors to improve its growth and reduce its cultivation costs. © Published under licence by IOP Publishing Ltd.